Validation of the Chick Embryotoxicity Screening Test (CHEST). A comparative study - Jelínek, R; Marhan, O (Functional and developmental morphology, 1994)
With the aim of investigating the predictive value of the Chick Embryotoxicity Screening Test (CHEST) with respect to regulatory rat-rabbit procedures, we compared the results of testing 50 chemicals of different pharmacological properties. Besides all being tested in the alternative technique, 27 substances were tested both in rats and rabbits, 22 only in the rat, and one only in the rabbit, respectively. The predictive value of CHEST with respect to the both official whole-animal procedures was found satisfactory, exhibiting about 80% consistent results. It is argued that the purpose of alternative testing methods is not in replacing the official routine procedures, but in contributing to the development of new predictive systems based on recent teratological knowledge.
Keywords: potkani Wistar; reprodukovatelnost výsledků; Chick Embryo; králíci; Toxicity Tests; Rats; testy toxicity; Animals; krysa rodu Rattus; Predictive Value of Tests; Rats, Wistar; Reproducibility of Results; prediktivní hodnota testů; zvířata; Rabbits; kuřecí embryo